Political economy analysis of the performance‐based financing programme in Afghanistan - Ahmad Shah Salehi; Karl Blanchet; Anna Vassall; Josephine Borghi (BMC, 2021)
Abstract Background Performance-based financing (PBF) has attracted considerable attention in recent years in low and middle-income countries. Afghanistan's Ministry of Public Health (MoPH) implemented a PBF programme between 2010 and 2015 to strengthen the utilisation of maternal and child health services in primary health facilities. This study aimed to examine the political economy factors influencing the adoption, design and implementation of the PBF programme in Afghanistan. Methods Retrospective qualitative research methods were employed using semi structured interviews as well as a desk review of programme and policy documents. Key informants were selected purposively from the national level (n = 9), from the province level (n = 6) and the facility level (n = 15). Data analysis was inductive as well as deductive and guided by a political economy analysis framework to explore the factors that influenced the adoption and design of the PBF programme. Thematic content analysis was used to analyse the data. Results The global policy context, and implementation experience in other LMIC, shaped PBF and its introduction in Afghanistan. The MoPH saw PBF as a promise of additional resources needed to rebuild the country's health system after a period of conflict. The MoPH support for PBF was also linked to their past positive experience of performance-based contracting. Power dynamics and interactions between PBF programme actors also shaped the policy process. The PBF programme established a centralised management structure which strengthened MoPH and donor ability to manage the programme, but overlooked key stakeholders, such as provincial health offices and non-state providers. However, MoPH had limited input in policy design, resulting in a design which was not well tailored to the national setting. Conclusions This study shows that PBF programmes need to be designed and adapted according to the local context, involving all relevant actors in the policy cycle. Future studies should focus on conducting empirical research to not only understand the multiple effects of PBF programmes on the performance of health systems but also the main political economy dynamics that influence the PBF programmes in different stages of the policy process.